Consumer behavior towards organic food : The case of Vietnam - Thu, Dang Minh; Kottika, Efthymia, 1982-; Karlíček, Miroslav, 1979-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
This current paper was a study on consumer behavior towards organic food in Vietnam. The purpose of this study is to investigate the factors that influence organic food consumption and provide an overview of the organic food sector in Vietnam. Thus, qualitative approaches were used to interpret the data collected from an in-depth interview with Vietnamese consumers. The search results revealed that there is a certain gap between consumers' awareness and actual behavior when it comes to purchasing organic food, leading to the fact that consumption in this market is still uneven across regions. External and internal stimuli, on the other hand, have a favorable effect on customers. The results also include aspects that promote and hinder the desire to buy organic food, with health being the main driver for the buyer, while the price is a barrier to purchase. Consumers are generally conscious of the benefits of organic produce, but this does not imply that they will purchase it.
Vedoucí práce: Efthymia Kottika
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses